Pengaruh Electronic Word of Mouth terhadap Minat Beli pada Media Sosial Twitter di Jawa Barat dan Dki Jakarta - Arianis Chan; Eliezer Eramukti Handoko; Lina Auliana (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
This study aims to determine the influence of electronic word of mouth of @NetflixID on buying interest through a survey of Twitter users in West Java and DKI Jakarta. The object is electronic word of mouth (independent variable) and buying interest (dependent variable). The research method used is descriptive verification analysis with a survey design to 101 Twitter user respondents who read tweets of @NetflixID in West Java or DKI Jakarta. The questionnaire used to measure the influence the electronic word of mouth by @NetflixID on buying interest. The results showed there was a strong and positive relationship between electronic word of mouth on buying interest on @NetflixID. Expressing positive feelings was the the highest percentage dimension for the electronic word of mouth variable, buying interest has the highest percentage on the variable interested to try and want to buy.